Physiological response to cycling with variable versus constant power output - Borg Kolsung, E.; Ettema, G.; Skovereng, K. (Frontiers in Physiology, 2020)
Introduction: Variable power output (VP) is one of the main characteristics of a road cycling mass-start. Tolerating VP during outdoor road cycling highly influences performance. There is a lack of continuous and comprehensive measurements during this power condition. Accordingly, the aim of the present study was to investigate physiological response to VP vs. constant power output (CP) as well as the perceived exertion of these two power conditions, and to investigate if variations in power output which span above lactate threshold (LT), differ from variations below LT.